2017
DOI: 10.2337/dc16-2724
|View full text |Cite
|
Sign up to set email alerts
|

Renal Handling of Ketones in Response to Sodium–Glucose Cotransporter 2 Inhibition in Patients With Type 2 Diabetes

Abstract: OBJECTIVEPharmacologically induced glycosuria elicits adaptive responses in glucose homeostasis and hormone release, including decrements in plasma glucose and insulin levels, increments in glucagon release, enhanced lipolysis, and stimulation of ketogenesis, resulting in an increase in ketonemia. We aimed at assessing the renal response to these changes. RESEARCH DESIGN AND METHODSWe measured fasting and postmeal urinary excretion of glucose, b-hydroxybutyrate (b-HB), lactate, and sodium in 66 previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 35 publications
5
128
2
3
Order By: Relevance
“…Increased erythropoietin and a median 7% increase in red blood cell mass, measured with 51 Cr-labeled erythrocytes, were observed in a small study (n = 30) of the SGLT2 inhibitor dapagliflozin in patients with type 2 diabetes (26). In a larger study, a mean increase in erythropoietin of 30-40% was observed 4 weeks after initiating empagliflozin, which may be related to changes in blood flow between the renal cortex and the medulla (27). The extent to which this mechanism contributes to the CV benefits observed with empagliflozin is unclear, however.…”
Section: Discussionmentioning
confidence: 99%
“…Increased erythropoietin and a median 7% increase in red blood cell mass, measured with 51 Cr-labeled erythrocytes, were observed in a small study (n = 30) of the SGLT2 inhibitor dapagliflozin in patients with type 2 diabetes (26). In a larger study, a mean increase in erythropoietin of 30-40% was observed 4 weeks after initiating empagliflozin, which may be related to changes in blood flow between the renal cortex and the medulla (27). The extent to which this mechanism contributes to the CV benefits observed with empagliflozin is unclear, however.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CV disease markers, an important observation was that regardless of RAS inhibition at baseline, haematocrit levels were increased, which could indicate either volume contraction or increase in erythropoiesis . Volume contraction corresponds to one of the main hypotheses for the CV benefits observed in the SGLT‐2 inhibitor CVOTs: an increase in haematocrit, resulting in beneficial cardiac haemodynamics .…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes, increased expression and activity of SGLT2, and fully activated SGLT1, account for almost 50 g of sodium, which may represent over 10% of the filtered sodium load, may be reabsorbed via SGLT‐dependent pathways . Although post meal urinary sodium excretion, in addition to urinary glucose excretion, was increased from baseline, both acutely and chronically, by administration of an SGLT2 inhibitor (SGLT2i), little is known about the association of sodium intake with the clinical effects of SGLT2is. Fundamental experiments indicated that genetic and pharmacological inhibition of SGLT2 attenuated primary proximal tubule hyper‐reabsorption of sodium and glucose in diabetic models and, thereby, lowered glomerular hyperfiltration via TGF .…”
Section: Introductionmentioning
confidence: 99%